OS3.3 Development of an EORTC questionnaire measuring instrumental activities of daily living (IADL) in patients with brain tumours: phase I-III. (6th September 2019) - Oort, Q; Dirven, L; Boele, F; Grant, R; Sato, H; Talacchi, A; Young, T; Reijneveld, J C; Taphoorn, M J B
Abstract: BACKGROUND: In brain tumour patients, impairments in every day functioning can impact quality of life, and are therefore an important outcome in both clinical trials and practice. One way to measure every day functioning is with an activities of daily living (ADL) questionnaire. Instrumental ADL (IADL) are the cognitively more complex activities, that are essential to function autonomously within society. Cognitive decline may therefore negatively impact IADL, making these activities particularly relevant to brain tumour patients. The aim of this study is to develop a reliable and valid questionnaire to measure IADL in primary malignant and metastatic brain tumour patients. MATERIAL AND METHODS: The questionnaire development study followed the standard European Organisation for Research and Treatment of Cancer (EORTC) four phase methodology: (I) generation of activities list, (II) construction of item list, (III) pre-testing, and (IV) field testing. This report covers phases I-III. To ensure cross-cultural validity, participants were recruited from different countries (The Netherlands, United Kingdom, Italy, Austria and Japan). In phase I, potential activities were identified based on a literature review and in-depth interviews with patients, proxies and healthcare professionals. In phase II, activities were turned into items, and translated into all required languages by the EORTC Translation Unit. In phase III, the item list was pre-tested in patient-proxy dyads. In accordance with predetermined decision rules to reduce items, final items were selected, and preliminary psychometric properties (i.e. factor structure, validity, reliability) were assessed. RESULTS: Phase I (N=44 dyads) resulted in 59 IADL activities which were converted into 59 items in phase II. In phase III, N=85 dyads completed and reviewed this item list. The item list was subsequently reduced to 32 items. An exploratory factor analysis indicated several items measuring similar underlying constructs (e.g. domestic life and using computer/smartphone) showing acceptable to good (α≥0.7) internal consistency (range α=0.69–0.89). Seven items were less related to these underlying constructs (e.g. work or managing your own medication), and therefore single items. Construct validity, measured with known-group comparisons analyses between cognitively impaired and unimpaired patients, showed significant differences in scores between the two groups on some scales and several single items. CONCLUSION: The currently developed EORTC IADL-BN32 questionnaire can be a valuable asset in assessing IADL functioning in brain tumour patients, but further validation in phase IV is required and is planned.